SOME QUESTIONS OF GEOLOGICAL-ECONOMIC ESTIMATION OF HARD MINERAL DEPOSITS (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
In this article the nature of typical errors of prospecting works is considered. Values of specific capital investments and the cost price of basis cycles of mountain-concentrating manufacture are resulted, with the help of which it is possible to be guided at detailed calculations.
Keywords: stocks; estimation; errors; the mining enterprise; productivity; capital investments; the cost price; specific indicators